A Narrative Inquiry of Students’ Self-Directed Learning in EFL Speaking Class through YouTube - Nur, Sahril; Butarbutar, Ranta (Har Press Indonesia, 2022)
This study aims to reveal student’s perceptions through narrative inquiry when learning English through YouTube. Previous studies insisted that learners have made several attempts to foster their English language, both via teacher-guided and self-directed study, in recognition of the advantages of speaking as a foreign language. Exploring learners' accounts of their self-directed learning in EFL speaking class using YouTube is the focus of the present research. Online interviews were conducted with four students as the research participants. In this line, the research presented three narratives—behavior-oriented, instructional, and evaluation—to describe students' motivations for completing SDL. Aside from the primary important elements influencing students' SDL with respect to their perspective, the study is aware of several limitations, including the sample size and research design. We urge more research on classroom participation studies in light of this. We anticipate that this study will contribute to the conversation on developing SDL curricula.